Dynamics of phoD- and gcd-Harboring Microbial Communities Across an Age Sequence of Biological Soil Crusts Under Sand-Fixation Plantation - Zhao, Xingxing; Zhang, Ying; Cui, Zhenbo; Peng, Lu; Cao, Chengyou (Frontiers in Microbiology, 2022)
Biological soil crusts (BSCs) are important for restoring vegetation and improving soil fertility in arid or semiarid desertified land. However, studies on the contribution of BSC microbes to phosphorus (P) transformation remains limited. The microbial diversity involved P transformation and its dynamic along BSC development should be examined to further understand the microbial regulatory mechanism of the P-cycling process. This paper investigates the soil properties, P fractions, and potential of P transformation across a chronosequence (0-, 8-, 20-, and 35-year) of the BSC under Caragana microphylla plantation on the moving sand dunes in Horqin Grassland, China. An abundance of phoD and gcd genes was detected, and the diversities and structures of phoD- and gcd-haboring microbial communities were illustrated via high-throughput sequencing. Soil nutrient content, activity of alkaline phosphomonoesterase, potential of organic P mineralization, and the abundance of phoD and gcd genes all linearly increased along with BSC age. The microbial quantity and species diversity of the phoD community were greater than those of gcd. BSC development increased the availability of inorganic P fractions, and both NaHCO3-Pi and NaOH-Pi were positively correlated with the abundance of the two genes and the activity of alkaline phosphomonoesterase. The phyla of Actinobacteria, Planctomycetes, and Proteobacteria and the family of Streptomycetaceae were the most dominant taxa in the phoD community, Proteobacteria was the dominant phylum in the gcd community in BSC soils, and Rhizobium and Planctomyces were the most dominant genera. The dominant taxa quantitatively responded to soil property improvement, but the basic compositions and dominant taxa did not change along with BSC development. The structures of phoD and gcd communities were linked to soil properties, and the increased pH, electrical conductivity, total N, NH4–N, and availabe K tend to be the direct affecting factors.